Bauran Pemasaran dan Demografi Pelanggan Terhadap Kinerja Pemasaran Ritel dengan Assortment sebagai Variabel Intervening - Nicko Falih; Hadi Sasana; Budi Rahardjo (Fakultas Ekonomi Universitas Islam 45, 2022)
Retail stores in the Mertoyudan area, which are sponsored by the Sampoerna Ritel Community (SRC) have experienced a continuous decline in sales. The SRC chairman confirmed the decline was due to many complaints from consumers who did not get the goods they were looking for. The research method used in this study is a quantitative method. The data used is primary data. The population in this study were customers of the SRC retail store in Mertoyudan, the sampling technique used was purposive sampling technique. Data analysis technique using Partial Least Square Structural Equation Model (PLS SEM) and processed using Smart PLS software. Based on the results of the study, it shows that the marketing mix variable has a negative and insignificant effect on marketing performance. Assortment and customer demographics have a real or significant influence on marketing performance. Assortment has a no mediation role on the relationship between the marketing mix and marketing performance. Assortment has a partial mediation role in the relationship between customer demographics and marketing performance.